Atezolizumab in combination with carboplatin plus nab‐paclitaxel for managing combined large‐cell neuroendocrine carcinoma: A case report - Rei Tsutsumi; Nobutaka Kataoka; Yusuke Kunimatsu; Izumi Sato; Mai Tanimura; Takayuki Nakano; Keiko Tanimura; Takayuki Takeda (Respirology Case Reports, 2022)
Abstract Large‐cell neuroendocrine carcinomas (LCNECs), categorized as high‐grade neuroendocrine carcinomas, account for approximately 3% of resected lung cancers. LCNECs containing other components are called ‘combined LCNECs’ and have no standard treatment. A 73‐year‐old male with a metastatic brain tumour from a combined LCNEC of the lung containing adenocarcinoma and sarcomatoid components was referred to our department. The patient was treated with chemotherapy consisting of carboplatin and nanoparticle albumin‐bound (nab)‐paclitaxel in combination with atezolizumab, which was decided in accordance with the histological evaluation of the components. This treatment resulted in partial response and remained durable for 12 months with an ongoing regimen. The current case suggests that the constituents of chemoimmunotherapy should be selected in accordance with the reported efficacy of relevant regimens for each component of the combined LCNEC.